2003
DOI: 10.1080/0165025024400173
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural study of the childhood developmental trajectory of attention and impulse control

Abstract: The maturation lag model explains inattention and impulsivity in Attention Deficit Hyperactivity Disorder (ADHD) as delayed maturation along a normal developmental trajectory. The concept of a cross-culturally uniform developmental trajectory is tested by a comparison of the performance of 212 Mexican school children on the Test of Variable Attention (TOVA) with the performance of populations previously studied. An observed pattern of decreasing errors of omission (indicating improving ability to sustain atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(34 reference statements)
1
4
0
1
Order By: Relevance
“…Other genetic factors may be influential – for example, it has been suggested that East Asian and US Hispanic children may have lower rates of ADHD relative to Euro‐American or British children (Brewis et al . , Oh & Lewis ). Oh and Lewis (, p. 97) suggested that one way to clarify differences in biologic or genetic and social (cultural) contributions to self‐regulation is to study children assimilating to other cultures.…”
Section: Discussionmentioning
confidence: 96%
“…Other genetic factors may be influential – for example, it has been suggested that East Asian and US Hispanic children may have lower rates of ADHD relative to Euro‐American or British children (Brewis et al . , Oh & Lewis ). Oh and Lewis (, p. 97) suggested that one way to clarify differences in biologic or genetic and social (cultural) contributions to self‐regulation is to study children assimilating to other cultures.…”
Section: Discussionmentioning
confidence: 96%
“…10 in the onlineonly Data Supplement). As CE is known to be related to a lack of inhibition against impulsivity [22], inhibition likely develops into the 30s. Carriere et al [23] also suggested that sustained attention developed into early adulthood and the OE decreased with age but rarely changed after the 20s.…”
Section: Samentioning
confidence: 99%
“…Researchers including Brewis, Schmidt, and Casas, (2003) are examining self-regulatory practices across cultures such as African American, Asian, European and Mexican. Previously, typically developing children were the focal point of research, but now the study of self-regulation branched to children with many different intellectual, behavioral and developmental capacities.…”
Section: Three Intervalsmentioning
confidence: 99%